Research of the Self-Reflection and Insight Status of Coaches on Active Duty - Eyyup Yıldırım, Oğuzhan Altungül, Mesut Bulut, Ömer Faruk Tutar (Pakistan Journal of Medical & Health Sciences, 2022)
Background: The universe of the study was created by active duty coaches, while the sample was made up of 165 active duty coaches who were randomly selected, limited to Elazig. Aim: The study aims to examine the self-reflection and insight of active-duty coaches in Elazig province. Methods: Personal information form and "Self-Reflection and Insight Scale" were used to examine the self-reflection and insight status of the active-duty coaches who participated in the study, and the frequency, percentage, t-test in binary groups, one-way variance analysis in multiple groups (Anova), as well as TUKEY test was used to find differences between groups. Results: Considering the total average values obtained from the Self-Reflection and Insight Scale; It was observed that there was no significant relationship between the variables according to the statistical evaluation made in terms of gender, the branch you are a coach, the state of education, coaching experience status. Although the total average score was close to each other in the separation between age groups with significant associations, a significant relationship was found between ages 41 and older and 26-30 years of age in the size of self-reflection. It was found that coaches aged 41 and over were more likely to self-reflect on the events they were exposed to than coaches aged 26-30. Conclusion: There was also a significant difference in the size of self-reflection in the marital status variable, married coaches were more likely to reflect on themselves than single coaches.